Syntrophic LCFA-degrading microbial ecosystems - Salvador, A. F. (2010)
Long-chain fatty acids (LCFA) are energy-rich compounds, which are abundantly present in raw and waste materials. Thus, wastewaters that contain LCFA may yield high levels of methane in an anaerobic digestion process. Biogas formation from LCFAcontaining wastewater is a sustainable technology that warrants further investigation, specifically in terms of more fundamental microbiological aspects. The aim of this work is to get more insights into the syntrophic microbial communities that degrade LCFA anaerobically. Bacterial shifts of a mesophilic sludge incubated in the presence of palmitic, stearic or oleic acid was estimated by means of automated ribosomal intergenic spacer analysis (ARISA). Slightly differences were observed between the communities incubated with saturated LCFA (palmitic and stearic acids) and the ones of the blank assay. On the other hand, evident changes were found between ARISA profiles of the communities that were incubated with oleic acid and the ones obtained for the blank assay. These results suggest that the microbial communities that degrade saturated fatty acids are very close to each other and different from the ones that degrade unsaturated fatty acids.